Features force between the foot and performance of special-based tests young basketball players - S.V. Stroganov (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Purpose . A quantitative analysis of biomechanical force interactions between the foot and the support when the athletes special tests. Material and methods . In the experiment involved 30 young athletes aged 7-8 years who are at the stage of initial training. Subjects performed four tests: jump up from their seats repulsion two feet, jump up and down with one foot repulsion run, stop step, jump stop. Results . As a result of studies to obtain quantitative values of reference indices interactions as the maximum reaction force impulse force, force gradient, the reference duration, and other interactions. Revealed that when jumping forward and upward to run and jump and step stops the horizontal component of force production is from 38 to 73 % of the resulting value. Conclusions . Significant power load on the musculoskeletal system and in particular the foot of young basketball players can lead to abnormalities in the foot. In connection with what the training process should include funds for the correction and prevention of foot function.